PENGARUH SERVICE QUALITY, FOOD QUALITY DAN ENVIRONMENT TERHADAP LOYALITAS PELANGGAN YANG DIMODERASI OLEH BRAND IMAGE (The Effect of Service Quality, Food Quality, and Environment on Customer Loyalty in Brand Image as Moderating) - Rahmayunita Rahmayunita; Rahmat Madjid; Nasrul Nasrul (Pascasarjana Universitas Halu Oleo, 2019)
This study is aimed to determine the effects of service quality, food quality and environment on customer loyalty of Padang cuisine in Sederhana Restaurant, Kendari and the role of brand image as a moderating effect of service quality, food quality and environment on customer loyalty of the restaurant. The sample of this study was 110 customers and used purposive sampling as sampling technique. Applying Partial Least Square (PLS) analysis, the results show that service quality has no significant effect on customer loyalty, while food quality and environment have a significant effect on customer loyalty. Furthermore, brand image acts as a moderating effect of service quality on customer loyalty. However, in terms of food quality and environment, it cannot act as a moderating variable.Keywords: Service Quality, Food Quality, Environment, Brand Image, Customer Loyalty